Figurative Language and Affective Meaning in Jennifer Lopez’s Empowerment Songs - Dhira Ferda Wulandari (IREELL: Indonesian Review of English Education, Linguistics, and Literature, 2025)
The gender-based oppression faced by women has led to the rise of empowerment movements that reach into the music media. Therefore, songs that carry messages of empowerment are often from the perspective of women, expressing the voices of a group that has long been marginalized. This research employed a descriptive qualitative method to analyze how figurative expressions contribute to the portrayal of women’s empowerment and to examine the affective meanings that convey the messages of empowerment in Jennifer Lopez’s “Ain’t Your Mama” and “Limitless” song lyrics. The findings reveal that in “Ain’t Your Mama,” the figurative expressions used include metaphor, metonymy, symbol, and hyperbole, while in “Limitless,” they include metaphor, symbol, paradox, and irony. Each of these figurative expressions in the songs contributes to strengthening the message of empowerment. As for the affective meaning, “Ain’t Your Mama” expresses its message more confrontationally, while in “Limitless,” the tone is more reflective and motivational. Figurative language and tone in the songs enable listeners to personally feel and deeply understand the empowering message behind the lyrics.